Transfer learning of tissue photon interaction in optical coherence tomography towardsin vivo histology of the oral mucosa - Sheet, Debdoot; Banerjee, Satarupa; Karri, Sri Phani Krishna; Bag, Swarnendu; Anura, Anji; Giri, Amita; Paul, Ranjan Rashmi; Pal, Mousumi; Sarkar, Badal C.; Ghosh, Ranjan; Katouzian, Amin; Navab, Nassir; et al. (2014 IEEE 11th International Symposium on Biomedical Imaging, ISBI 2014, 2014)
Oral cancer evolves from different premalignant conditions and the key to save lives is through diagnosis of early symptoms. The conventional practice of post biopsy histopathol-ogy reporting is dependent on specificity of sampling site and optical coherence tomography (OCT) imaging is clinically used for guidance. Clinicians infer the tissue constitution by interpreting intensity images and are challenged by interand intra-observer variability. In this paper we propose transfer learning of tissue specific photon interaction statistical physics in swept-source OCT for characterizing the oral mu-cosa with the aim of reducing this reporting variability. The source task models statistical physics of ballistic and near-ballistic photons and its intensity attenuation and target task learns the parameters obtained by solving the source task to identify co-located heterogeneity of tissues. Performance is compared with conventional histopathology of healthy, premalignant and malignant oral lesions supporting its use towards in vivo histology of the oral mucosa for pre-biopsy screening.
CRIS-Team Scopus Importer:2023-03-08
Keywords: In vivo histology; Optical coherence tomography; Oral cancer; Tissue characterization; Transfer learning